1999
DOI: 10.1097/00000441-199911000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Physiologic Changes of Morbid Obesity

Abstract: Extreme obesity is associated with a reduction in ERV, FVC, FEV1, FRC, FEF25-75%, and MVV. However, contrary to prior reports, D(LCO) is not elevated. These effects are only partially explained by smoking.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
161
3
20

Year Published

2002
2002
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 212 publications
(196 citation statements)
references
References 17 publications
12
161
3
20
Order By: Relevance
“…Biring et al 22 also used spirometry in 43 morbidly obese patients and observed that ERV was significantly reduced due to obesity, a fact attributed to reduced pulmonary compliance, to the weight of the abdomen on the chest wall and to weakening of the respiratory musculature.…”
Section: Correlation Between Percent Loss Of Weight Excess and Pulmonmentioning
confidence: 99%
“…Biring et al 22 also used spirometry in 43 morbidly obese patients and observed that ERV was significantly reduced due to obesity, a fact attributed to reduced pulmonary compliance, to the weight of the abdomen on the chest wall and to weakening of the respiratory musculature.…”
Section: Correlation Between Percent Loss Of Weight Excess and Pulmonmentioning
confidence: 99%
“…[4][5][6][7][8][9][10] The most frequent pulmonary function tests (PFTs) findings are reduced expiratory reserve volume (ERV), functional residual capacity (FRC) and total lung capacity (TLC), [4][5][6]9 which are generally related to alterations in chest wall mechanics induced by an increased abdominal load. 8 These alterations reduce total respiratory compliance.…”
Section: (Ohs)mentioning
confidence: 99%
“…obesity on respiratory disease, there are clear effects on pulmonary function [3,4]. Cross-sectional studies have demonstrated an inverse relationship between forced expiratory volume in 1 s (FEV 1 ) and both BMI and waist circumference [5,6]. This is of particular importance because FEV 1 is an independent predictor of all-cause mortality and a strong risk factor for cardiovascular disease, stroke and lung cancer [7].…”
Section: Introductionmentioning
confidence: 99%